Prevalence and related factors of irregular menstrual cycles in Korean women: the 5th Korean National Health and Nutrition Examination Survey (KNHANES-V, 2010-2012) - Eun-Kyung Jung; Seok-Won Kim; Sun-Myeong Ock; Kyu-In Jung; Chan-Hee Song (Taylor & Francis Group, 2018)
Introduction: There have been few population-based studies reporting medical, lifestyle and psychological factors associated with irregular menstrual cycles. This study aimed to elucidate the prevalence and related factors of irregular menstrual cycles in Korean women. Methods: Cross-sectional data from the 5th Korean National Health and Nutrition Examination Survey were used. Eligible women were 19-40 years old, not currently taking oral contraceptives or using intrauterine devices, and not currently pregnant or breast feeding, and had no medical history of hysterectomy, thyroid diseases, cancers or renal failure. Finally, 3194 premenopausal women were recruited in this study. The prevalence and related factors of irregular cycles were obtained using a general linear model and logistic regression analyses in a complex sampling design. Results: The prevalence of irregular cycles was 14.3%. Age and high-education level were associated with lower odds ratios (ORs) for irregular cycles (OR 0.91, 95% confidence interval (95% CI) 0.87-0.96, and OR 0.58, 95% CI 0.38-0.88, respectively). The ORs of body mass index, perceived stress and depressive mood were 1.05 (95% CI 1.01-1.10), 1.46 (95% CI 1.11-1.92) and 2.07 (95% CI 1.18-3.63), respectively. Conclusions: Age, perceived stress, body mass index, depressive mood and education level, rather than obstetric factors or metabolic diseases were significant factors associated with irregular menstrual cycles in Korean women. Of these factors, perceived stress is the most significant factor associated with increased irregular menstrual cycles.